Instilling Moral Values through Dulmuluk Theater: A Qualitative Study on Character Education in Middle School Students - Notosutanto Arhon Dhony, Nugroho; Wadiyo, Wadiyo; Sahid, Nur; Cahyono, Agus (Universitas Negeri Padang, 2025)
This study aims to identify the values of moral character contained in the traditional Dulmuluk theater and to analyze the implementation and its impact on the character development of students. The research method employed is qualitative phenomenology, with an interpretative approach to the participants' experiences in theater activities. Data were collected through observations, interviews, and documentation, which were then analyzed using data reduction and categorization techniques based on the interactive analysis model by Miles and Huberman. In total, there were 20 subjects involved in this study. The results indicate that traditional Dulmuluk theater can shape students' character in various aspects, such as discipline, honesty, responsibility, cooperation, as well as social and cultural awareness. The interactions during rehearsals and performances play a significant role in fostering moral awareness, self-control, and togetherness. Evaluations of the cognitive, affective, and psychomotor domains also show that performing arts-based learning can enhance students' social skills and empathy. As a recommendation, this study suggests that the traditional Dulmuluk theater be incorporated as part of the character education curriculum in schools. Furthermore, further research is needed using longitudinal methods to measure the long-term impact of arts-based learning on the moral and social development of students.